Acupuncture at the P6 Acupoint to Prevent Postoperative Pain after Craniotomy: A Randomized, Placebo-Controlled Study. (18th March 2021) - Lv, Jian-Qin; Li, Peng-Cheng; Zhou, Li; Tang, Wen-Fu; Li, Ning
Abstract : Objective . Acute pain management after craniotomy can be challenging. Previous studies have shown inadequate pain control following the procedure. Oral medication can sometimes be delayed by postoperative nausea, and use of anesthetics may impair the assessment of brain function. We conducted this prospective study to evaluate the effect of acupuncture at the P6 acupoint on postoperative pain, nausea, and vomiting in patients undergoing craniotomy. Methods . The authors conducted a randomized, placebo-controlled trial among 120 patients scheduled for craniotomy under general anesthesia. 120 patients were randomly assigned into an acupuncture group or a sham acupuncture group. All patients received standardized anesthesia and analgesia treatment. Acupuncture was executed in the recovery room after surgery. For the acupuncture group, the P6 points on each wrist were punctured perpendicularly to a depth of 20 mm. Needles were retained for 30 min and stimulated every 10 min to maintain the De-Qi sensation. For the sham acupuncture group, sham points on each wrist were punctured perpendicularly to a depth of 5 mm. Needles were retained for 30 min with no stimulation during the duration. The postoperative pain scores, PONV, and dose of tramadol were assessed 24 h, 48 h, and 72 h after surgery. Results . A total of 117 patients completed the study. There was no statistically significant difference in baseline data between the two groups (P > 0.05 ). The VAS pain score of the acupuncture group was lower than that of the sham acupuncture group, and this difference was statistically significant (P = 0.002 ). There was no difference in pain scores between the two groups during 0–24 h and 48–72 h (P > 0.05 ). The incidence of vomiting in the acupuncture group was lower than that in the sham acupuncture group during the 0–24 h period (13.8% vs. 28.8%, P = 0.048 ). There was no difference in vomiting, however, during the 24–72 h period (P > 0.05 ). No significant differences were found in the degree of nausea and the dose of tramadol between the two groups at either time point in the acupuncture group and sham acupuncture group. Conclusion . The use of acupuncture at the P6 acupoint in neurosurgery patients did result in significantly lower pain scores and reduction in the incidence of vomiting after craniotomy. There were no significant side effects. Acupuncture at the P6 acupoint was well tolerated and safe in this patient population.